2015
DOI: 10.1002/lsm.22405
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary clinical investigation of cataract surgery with a noncontact femtosecond laser system

Abstract: Background and ObjectiveFemtosecond laser‐assisted cataract surgery (FLACS) is rapidly gaining popularity due to the improved consistency and predictability for capsulorhexis. This study aimed to investigate the preliminary clinical outcomes of FLACS with a noncontact femtosecond laser system.Patients and MethodsThis prospective study enrolled 25 eyes in the trial group underwent FLACS (LLS‐fs 3D, LENSAR, USA), and 29 eyes in the control group underwent conventional cataract surgery (Stellaris, Bausch & Lomb, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
2
25
1
1
Order By: Relevance
“…The heterogeneity might be attributed to various regional background, follow-up period, and surgical expertise. For instance, heterogeneity in refractive outcomes was significantly reduced (0%) after we removed the Chinese patients in Yu et al [16]. Further, we performed sensitivity analysis, and the nonreversed results confirmed that the conclusion of our meta-analysis was reliable.…”
Section: Discussionsupporting
confidence: 63%
“…The heterogeneity might be attributed to various regional background, follow-up period, and surgical expertise. For instance, heterogeneity in refractive outcomes was significantly reduced (0%) after we removed the Chinese patients in Yu et al [16]. Further, we performed sensitivity analysis, and the nonreversed results confirmed that the conclusion of our meta-analysis was reliable.…”
Section: Discussionsupporting
confidence: 63%
“…; Yu et al. ). Ultrasound energy may damage surrounding structures and may be implicated in the pathogenesis of endothelial cell loss (Dick et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Yu et al. ). The improvement in capsulotomy diameter and regularity has been linked with significantly better IOL centration (Nagy et al.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations